2020
DOI: 10.1002/alz.12077
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a Mediterranean diet and cognitive function in the Age‐Related Eye Disease Studies 1 & 2

Abstract: Introduction The objective was to determine whether closer adherence to the alternative Mediterranean Diet (aMED) was associated with altered cognitive function. Methods Observational analyses of participants (n = 7,756) enrolled in two randomized trials of nutritional supplements for age‐related macular degeneration: Age‐Related Eye Disease Study (AREDS) and AREDS2. Results Odds ratios for cognitive impairment, in aMED tertile 3 (vs 1), were 0.36 (P = .0001) for Modified Mini‐Mental State (<80) and 0.56 (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 63 publications
2
26
0
Order By: Relevance
“…Consumption of a diet rich in fish and other seafood, known to provide significant quantities of TMAO [ 83 ], associates with a reduced risk of cognitive decline [ 84 , 85 ] and protection against cerebrovascular disease [ 86 ]. These effects have in large part been attributed to beneficial actions of the omega-3 polyunsaturated fatty acids [ 87 ], although there is little evidence that their direct supplementation improves cognitive function [ 88 ] or stroke risk [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of a diet rich in fish and other seafood, known to provide significant quantities of TMAO [ 83 ], associates with a reduced risk of cognitive decline [ 84 , 85 ] and protection against cerebrovascular disease [ 86 ]. These effects have in large part been attributed to beneficial actions of the omega-3 polyunsaturated fatty acids [ 87 ], although there is little evidence that their direct supplementation improves cognitive function [ 88 ] or stroke risk [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, continuous exposure to Hg is very likely in the Jamaican community via fish consumption. On the other hand, dietary intake of seafood and fish is the main source of omega-3 polyunsaturated fatty acids (PUFA) in humans that play an important role in human health [ 93 ], brain development [ 94 ] and cognitive performance [ 95 , 96 , 97 ]. Since our study design is matched case-control and the measurement of exposure to the six metals including mercury took place at the time when the children were evaluated to confirm their ASD status at age 2–8 years, we are unable to establish temporality of the associations we reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…While a significant association was seen in the present analyses with the MedDiet and MIND diet within a shorter follow-up duration with some cognitive function assessments compared with other prospective cohort studies that have been conducted, this relationship was not found with the DASH diet. While MedDiet has been associated with a lower risk of cognitive impairment, it has not always been associated with a slower decline in cognitive function ( Keenan et al, 2020 ). Inconsistent findings have previously been observed with the DASH diet ( van den Brink et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%